Análise da correlação de indicadores socioeconômicos com a geração de resíduos nos munícipios paraenses - FREITAS, Lara Grazielle Sousa (2024)
The study analyzes the correlation between socioeconomic, demographic and consumption indicators with the generation of solid waste in municipalities in the state of Pará, Brazil, for the purpose of identifying correlation patterns that support and assist in the formulation of strategies for the sustainable management of these materials. This is a quantitative and exploratory research that uses Principal Component Analysis (PCA) to evaluate indicators collected in 116 of the 144 municipalities in Pará. The indicators used in the analysis were Population (POP), Gross Domestic Product (GDP), Municipal Human Development Index (IDHM), Firjan Municipal Development Index (IFDM), Gini Index (GI), Electricity Consumption (CE), Water Consumption (CA) and Waste Generation (GR), which were obtained through secondary data from the Brazilian Institute of Geography and Statistics (IBGE), the Amazon Foundation for Studies and Research Support (FAPESPA), the Institute of Economic and Applied Research (IPEA DATA) and the National Sanitation Information System (SNIS). The techniques used include data standardization using the Z-score method and the use of The Unscrambler software, version 9.7, for ACP. The research revealed positive correlation patterns between GR and indicators such as IDHM, IFDM, GI, POP, GDP per capita, CE and a strong correlation with CA. It was found that better economic conditions and quality of life are associated with the increasing generation of municipal waste. Furthermore, population data also contributed to greater amounts of waste generated. These results highlight the importance of considering socioeconomic factors when formulating public policies for waste management, aiming to reduce negative environmental impacts and promote sustainable practices.